The robes of the feudal baronage of Scotland - Innes, Thomas (Proceedings of the Society of Antiquaries of Scotland, 1946)
The Baronage is an Order derived partly from the system in which the patriarch held his country "under God", and partly from the later feudal system. The robes and insignia of the Baronage trace back to both these forms of tenure. A history of the feudal system as applied to Scotland is presented in some detail. The development and evolution of the ceremonial attire is described and illustrated.